Fighters across frontiers : Transnational resistance in Europe, 1936-48 - Tames, Ismee; Gildea, Robert (Book collections on Project MUSE., 2020)
This landmark book, the product of years of research by a team of two dozen historians, reveals that resistance to occupation by Nazi Germany and Fascist Italy during the Second World War was not narrowly delineated by country but startlingly international. Tens of thousands of fighters across Europe resisted 'transnationally', travelling to join networks far from their homes. These 'foreigners' were often communists and Jews who were already being persecuted and on the move. Others were expatriate business people, escaped POWs, forced labourers or deserters. Their experiences would prove personally transformative and greatly affected the course of the conflict. From the International Brigades in Spain to the onset of the Cold War and the foundation of the state of Israel, they played a significant part in a period of upheaval and change during the long Second World War.